Synthesis of Epoxide as Intermediate Compounds for Biolubricant Production from Crude Palm Oil - R. Arie Hartawan; Muhammad Said; Muhammad Faizal; Juni Prianto; Miratna Juwita; Nabila Aprianti (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2022)
The use of biolubricant must be encouraged to reduce environmental pollution from non-biodegradable lubricants by utilizing crude palm oil. This study aims to synthesize epoxide compounds from crude palm oil (CPO) as intermediate compounds to produce Biolubricant and determine the kinetic reaction and the enthalpy of the epoxide reaction. The process of synthesizing epoxide was carried out in a stirred reactor. The epoxidation reaction occurred at 60, 70, and 80 °C for 30 – 180 min with 30 min intervals using 1, 2, and 3% H2SO4 as catalysts. The highest conversion was obtained at a reaction temperature of 70 °C at 90 min using 2% H2SO4 of 87.59%. The characteristics of the epoxide compound produced have a density of 0.951 g/cm3, a kinematic viscosity of 44.388 CSt, an acid number of 4.32 mg NaOH/g oil, and oxirane number of 5.731 g/cm3. The reaction kinetic constant and enthalpy were 0.0104 mol/mL min and 10494.762 J/mol. The synthesized epoxide from crude palm oil was proven to be a suitable intermediate compound for biolubricant production.